Language Contestation In Garuda Wisnu Kencana Tourism Area - Adi Wira Laksana, I Made; Mulyawan, I Wayan; Weddha Savitri, Putu (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study investigates language contestation in the linguistic landscape of Garuda Wisnu Kencana (GWK), a cultural tourism destination in Bali that serves both local and international visitors. The research aims to identify the types of signs in GWK and to analyze how Balinese, Indonesian, and English are represented and contested. Using a descriptive qualitative method with observation and photography, 168 signs were documented across three zones: Street Theatre (71), Kencana Souvenir (51), and Commercial Strip (46) during May–June 2025. The findings show that commercial signs (37.5%) and notice signs (36.3%) dominate, followed by name signs (19%) and mixed signs (7.1%). English is the most visible language, appearing in 43.5% of monolingual signs and frequently in bilingual Indonesian–English signs (41.7%). Indonesian is mainly used in regulatory signs, while Balinese functions symbolically with minimal monolingual presence. Zone-based variations reveal that Kencana Souvenir is strongly English-dominant, Commercial Strip highlights Indonesian in regulatory functions, and Street Theatre shows a more balanced distribution. The study concludes that tourism-driven commercialization shapes linguistic hierarchies and calls for signage policies that strengthen the visibility of local language and cultural identity.